STRATEGI PEMASARAN UMKM KERIPIK TEMPE DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Kevin Alfareza Alfareza; Henny Indrawati; Fenny Trisnawati (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study aims to determine the marketing strategy of tempe chips SMSe in Singingi District, Kuantan Singingi Regency. The research used a qualitative descriptive method which was carried out at UMKM Van Rafizky Tempe Chips. Sources of data were obtained from direct interviews with tempe chip MSME business owners through a questionnaire guide. The data analysis technique used is SWOT analysis to systematically identify various factors, formulate the driving and inhibiting factors for the growth and development of the Tempe Chips MSME business. Based on the results of the research, the marketing strategy implemented is a growth strategy through horizontal integration, by increasing product quality and diversifying flavors to meet consumer preferences, keeping the price of tempeh chips affordable, optimizing the use of various information media in increasing promotions, leveraging the power of the internet and the E-platform. -commerce to market products, add product innovation by making tempeh chips more varied and packaging more attractive. Keywords: Marketing Strategy, SMEs, SWOT Analysis